Influences of atmospherics on customer satisfaction and behavioural intentions in the restaurant industry: Evidence from an emerging economy - Mananage Shanika Hansini Rathnasiri; Pawan Kumar; Bindu Aggarwal; Kiran Nair; Narayanage Jayantha Dewasiri (PLoS ONE, 2025)
The emergence of the food service industry is among the most promising sectors that open many great opportunities for its development. Restaurants are also a part of the world’s economy. This is reflected in the increasing demand for high-quality, upscale dining experiences. The restaurant industry is well-positioned for future growth. However, few researchers have explored the impact of restaurant attributes on overall customer satisfaction and behavioural intentions in the context of fine dining restaurants. This study investigates how restaurant attributes influence overall satisfaction and behavioural intentions in an emerging economy such as India. To explore this relationship, we adopted the Stimulus-Organism-Response (SOR) theory proposed by Mehrabian and Russell (1974) [1]. The results show that restaurant attributes can lead to higher customer satisfaction rates, benefiting the industry. Restaurant attributes also play an essential role in creating a positive customer dining experience. Restaurant attributes help provide thoughtful customer service, such as assisting with menu items, remembering customers’ names, or providing helpful suggestions, which can also show customers that they are valued.